AB0707 Comparative effectiveness of secukinumab and golimumab in ankylosing spondylitis assessed by matching-adjusted indirect comparison using pivotal phase 3 clinical trial data. (15th June 2017) - Maksymowych, W; Choy, E; Yazici, Y; Walsh, J; Thom, H; Kalyvas, C; Fox, T; Gandhi, K; Jugl, S
Abstract : Background: No data are available from head-to-head RCTs between secukinumab 150 mg (SEC; an anti-IL-17A) and golimumab 50 mg (GOL; a TNFi) in patients with active ankylosing spondylitis (AS). Matching-Adjusted Indirect Comparison (MAIC) can be used to estimate comparative effectiveness and enables treatment outcomes to be compared across effectively balanced trial populations. MAIC is an established method in health technology assessments and NICE have published guidance on appropriate methodology, and especially for addressing imbalances in observed covariates between trials. 1 Objectives: To assess the comparative effectiveness of SEC and GOL up to week 24 using MAIC with pooled individual patient data (IPD) from the RCTs MEASURE 1 (M1) and MEASURE 2 (M2) and published aggregate data from the RCT GO-RAISE. Methods: Pooled M1 and M2 data were used to maximize the effective sample size (ESS) for SEC. IPD from the SEC arms of M1 and M2 (n=197) were weighted to match the published baseline characteristics of the GOL arm of GO-RAISE (n=138). Placebo arms were matched in the same way; placebo-adjusted comparisons were possible only until week 16 because patients could receive active treatment from this time onwards. Logistic regression was used to determine weights for age, sex, BASFI, disease duration, CRP and previous TNFi therapy. Recalculated outcomes from M1 and M2 (SEC, ESS=102; placebo, ESS=81) were compared with data from GO-RAISE (GOL, n=138; placebo, n=78). Pairwise comparisons – reported as odds ratios (ORs [95% CIs]) – were performed for ASAS 20, ASAS 40 and ASAS PR responses at nearest-equivalent time points across trials: week 12 (SEC)/14 (GOL), week 14 (GOL)/16 (SEC) and week 24 (SEC and GOL). Non-responder imputation (NRI) was available for all binary outcome data. Strict thresholds were avoided when interpreting p values, in line with American Statistical Association 2016 guidance. Results: There was no evidence of differences in ASAS 20 and ASAS 40 responses between SEC and GOL at weeks 12/14 and 14/16 (both placebo-adjusted). At week 24, non-placebo-adjusted ASAS 20 and ASAS 40 responses using NRI were higher with SEC than GOL (OR [95% CI]: 1.58 [0.93–2.69], p =0.089 and 1.58 [0.94–2.64], p =0.084, respectively). There was no evidence of differences in ASAS PR responses between SEC and GOL at weeks 12/14, 14/16 and 24. A sensitivity analysis conducted after adding BASDAI score to the matching parameters yielded similar results. Conclusions: There was no evidence of differences in ASAS responses between SEC and GOL in placebo-adjusted analyses. In non-placebo-adjusted analyses, SEC showed higher ASAS 20 and ASAS 40 responses than GOL at week 24. References: Phillippo DM et al. (2016) NICE DSU Technical Support Document 18. Available from: http://www.nicedsu.org.uk . Disclosure of Interest: W. Maksymowych Grant/research support from: AbbVie, Pfizer and Sanofi, Consultant for: AbbVie, Amgen, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Sanofi and UCB, E. Choy Grant/research support from: Pfizer, Roche and UCB, Consultant for: Chugai Pharma, Eli Lilly, Janssen, Novartis, Pfizer, Regeneron, Roche, R-Pharm and Sanofi, Y. Yazici Grant/research support from: Celgene, BMS and Genentech, Consultant for: Celgene, BMS and Novartis, J. Walsh Consultant for: Novartis, H. Thom Consultant for: Eli Lilly, F Hoffman-La Roche, Novartis Pharma AG and Pfizer, C. Kalyvas Employee of: Paid employee of the Mapi Group. The Mapi Group received funding from Novartis Pharma AG for this study, T. Fox Employee of: Novartis employee with stock, K. Gandhi Employee of: Novartis employee with stock, S. Jugl Employee of: Novartis employee with stock